Retrospective analysis of survival and safety of bevacizumab biosimilar and original drug combination chemotherapy in non-small cell lung cancer - Zhang, Xinyi; Chu, Xiaofei; Wang, Jun; Gu, Wenjing; Fu, Xiaoyan; Zhang, Jing; Wang, Congying; Han, Qinghui; Zhou, Jing; Zhang, Yongjing (Frontiers in Oncology, 2024)
IntroductionThe advent of bevacizumab has considerably transformed the therapeutic landscape for non-small cell lung cancer (NSCLC) patients devoid of specific genetic mutations. A pivotal milestone has been reached with the recent approval of a bevacizumab biosimilar, following rigorous phase III clinical investigations, poised to augment NSCLC therapeutic strategies.MethodsThis retrospective analysis encompasses a large-scale study conducted between January 2021 and December 2023, involving 1058 NSCLC patients (metastatic or locally advanced stages). The research design entailed a comparative assessment of the safety and efficacy profiles of combined therapies using the original bevacizumab and its biosimilar, adhering to RECIST v1.1 criteria. Adverse event grading was standardized using the National Cancer Institute’s CTCAE v5.0.ResultsNotably, the biosimilar demonstrated an objective response rate (ORR) of 29.79% in 606 patients, closely paralleling the 27.41% ORR observed in 452 patients receiving the original drug, with insignificant risk differences (-0.03) and a risk ratio of 0.987, affirming equivalence. Progression-free survival (PFS) was influenced by radiation status, treatment lines, and regimen combinations, while dosage intensity and genetic factors had negligible impacts. The incidence of treatment-emergent adverse events (TEAEs) was slightly higher in the biosimilar group (75.11%) versus the original drug group (72.78%), with grade 3 or more severe TEAEs occurring in 23.6% and 18.5% of patients, respectively (Detailed criteria for the definition and assessment of TEAEs have been added to the Methods section, including the use of the National Cancer Institute’s CTCAE v5.0 for grading).ConclusionsThe study affirms that bevacizumab biosimilars offer equivalent therapeutic efficacy and a similar safety profile to the originator product in the management of locally advanced or metastatic NSCLC. The tolerability of the toxicity profile, coupled with the absence of unforeseen adverse reactions, underscores the viability of biosimilar bevacizumab as a valuable addition to NSCLC treatment regimens. These findings also imply potential benefits for a broader patient population beyond clinical trial confines through the adoption of biosimilar beta-adrenergic blocking agents.